Hybrid coatings for orthopaedic implants formed by physical vapour deposition and microarc oxidation. (July 2022) - Gabor, Roman; Cvrček, Ladislav; Doubková, Martina; Nehasil, Václav; Hlinka, Josef; Unucka, Petr; Buřil, Matěj; Podepřelová, Adéla; Seidlerová, Jana; Bačáková, Lucie
Graphical abstract: Highlights: Unique combination of PVD and MAO techniques was used to prepare hybrid coatings to improve Ti-6Al-4V alloy properties. Prepared hybrid coatings with ZrTi exhibited improved corrosion and abrasion resistance, and a lower coefficient of friction. Hydrophilic oxide structure of prepared hybrid coatings increased osteogenic differentiation of human bone marrow mesenchymal stem cells in vitro . Combined use of MAO nad PVD techniques provides new possibilities of fine tuning the material surface layer properties. Abstract: This study is focused on the preparation of new hybrid layers intended for surface modification of Ti-6Al-4V alloys for potential orthopaedic and dental applications. Combination of the technology of physical vapour deposition (PVD) and subsequent micro-arc oxidation (MAO) was utilized for the deposition of Ti and ZrTi to form hybrid oxide layers. The oxide layers were prepared using an alkaline electrolyte with glycerol as an additive under micro-arc discharge conditions with different Si content on their surfaces. The hybrid ZrTi coatings with a Zr/Si structure achieved the best tribological properties described by a low friction coefficient of 0.3 and high abrasion resistance. There was also an increase in corrosion potential and polarization resistance of hybrid ZrTi coatings. Although the proliferation of human bone marrow mesenchymal stem cells was slower on these hydrophilic Ti and ZrTi coatings than both on uncoated Ti-6Al-4V and the reference tissue culture polystyrene dishes, both types of hybrid coating promoted greater osteogenic differentiation of these cells, indicated by approx. twice as high activity of alkaline phosphatase. The hybrid oxide layers newly developed in this study – especially the layers with Zr – are therefore promising for coating metallic bone implants.